Investigation of the Functional Properties of Some Origanum Species and Their Bioactive Components - Setenay Beril TEKİN; Ender Sinan POYRAZOĞLU; Yalçın GÜÇER (ISPEC Journal of Agricultural Sciences)
The genus Origanum is represented by 24 species in Turkey, with an endemism rate of 63%. The chemical compositions of essential oils obtained through hydro distillation from thyme species such as Origanum vulgare, Origanum onites, and Origanum minutiflorum, collected from various locations in the Aegean and Mediterranean regions, were determined by using GC-MS analysis. Furthermore, the antioxidant and antimicrobial activities of the essential oils were investigated. Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed that the major components of O. minutiflorum essential oils were carvacrol (67.86–84.95%), p-cymene (5.36–8.77%), and γ-terpinene (0.99–3.46%). In the case of O. onites essential oils, the major components were identified as carvacrol (30.01–71.96%), thymol (1.53–38.25%), p-cymene (3.90–10.07%), and γ-terpinene (2.25–5.07%). In the essential oil composition of O. vulgare samples collected from Alanya, the main components were found to be carvacrol (81.35%), linalool (10.17%), p-cymene (1.27%), thymol (1.21%), and β-caryophyllene (1.01%). For the purpose of antioxidant activity studies, the DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging activity assay was employed. Utilizing the DPPH method, the EC50 values of the investigated Origanum spp. were determined to range from 0.44 to 16.21 µL, with the lowest value observed for O. onites (0.44 µL) and the highest for O. vulgare (16.21 µL). Furthermore, essential oils at varying concentrations (5, 10, 20, 30, 40, 50, and 80 µL mL-1) were mixed with bacterial suspensions and plated in petri dishes to determine the number of surviving bacteria. The results indicated that Origanum essential oils exhibited strong antimicrobial activity against Escherichia coli O157:H7 and significantly reduced the numbers of Listeria monocytogenes (P<0.05).